Biological nutrient removal using sequencing batch bioreactor - Muhamad Yasin, Ismail (2009)
In order to control the eutrophication problems, the removal of phosphorus has been increasingly important. The biological phosphorus removal using sequencing batch reactor (SBR) was investigated using simulated municipal wastewater. Experiments were carried out in eight sequencing batch reactors (SBRs) at hydraulic retention time (HRT) of 5 d. The experiment is operated at loading rates (LR) of 5.0, 4.5, 4.0, 3.5 and 3.0 mg/L.d. The mixed cultured growth is increased with the increasing of LR according to the suspended solids readings. The graph of the suspended solid concentration, the phosphorus removal and the chemical oxygen demand (COD) removal is almost same which is increasing by time and loading rate. The higher the loading rate, the higher the value of suspended solid, phosphorus removal and COD removal. LR 5 mg/L.d shows the highest suspended solid (SS) concentration with average value of 846.24 mg/L. The highest value of phosphorus removal is at loading rate 5.0 mg/L.d with average removal of 57.38%. The COD removal is also highest at loading rate 5.0 mg/L.d with average removal of 64.33%. The removal was influenced by the biofilm growth according to the suspended solid readings. The highest SS reading give the highest removal for both phosphorus and COD. According to the Design Expert plotted, the highest phosphorus removal can be achieved at LR 5.0 mg/L with 56.89% removal. Same result in Design Expert for COD removal which give the highest removal of 61.69% at LR 5.0 mg/L.d. As for the SS concentration, the Design Expert determine that the optimum value of SS is at LR 5.0 mg/L.d with the value of 840.92 mg/L.